The wilder Muir the curious nature of John Muir - Muir, John 1838-1914 (Yosemite Conservancy, 2017)
A collection of John Muir's nature adventures, with contextualizing introductions at the beginning of each entry by Gisel
Keywords: Muir, John / 1838-1914; Naturalists / United States / Biography; United States / Description and travel; Naturalists; Travel; United States; Autobiographies; Biography; Biografie